Disclosure of conflicts of interest and credibility for the medical profession - Braillon A; Granger B (Dove Medical Press, 2015)
Alain Braillon,1,* Bernard Granger2,* 1Alcohol Treatment Unit, Amiens University Hospital, Amiens, 2Department of Psychiatry, Tarnier Hospital (AP-HP), Paris, France, *Both authors contributed equally to this workWe were surprised by an unbalanced review about nalmefene for alcohol dependence, wherein the authors had stated no conflicts of interest (COIs).1 The Editor in Chief and the Publisher were very professional when we stressed our concerns, and they must be commended. They accepted publication of a critical free evaluation based upon evidence where we also called for full disclosure of COIs.2 View the original Letter by Braillon and GrangerView the original article by Paille and Martini